If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3y = 2 Solving 4x + 3y = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 4x + 3y + -3y = 2 + -3y Combine like terms: 3y + -3y = 0 4x + 0 = 2 + -3y 4x = 2 + -3y Divide each side by '4'. x = 0.5 + -0.75y Simplifying x = 0.5 + -0.75y
| 13=-13y+3y | | 3x=7-x | | 2z+3-4z=3z-7 | | 9w+w= | | 8-4x=-6 | | 3(x+7)=26 | | 55=39-5c | | 4x(3x-1)= | | 3(5c-1)=4(3c+2) | | 4v^2=-11v-6 | | 6n-2=4n+6 | | 3x(x+5)= | | 2x^2-20x=-42 | | y+5+2y= | | 6x+5x=63 | | 4(n-1)=-8 | | y^2+9y=-20 | | 5y-2(y+4)=1 | | 3x^2-8x^7-2x^2=9x^7 | | 6x^2-8x-12=0 | | 2K(K+3)=-9 | | 2K(K+3)=9 | | 3(x-4)+15=2(x+3) | | 6y^2-6=0 | | 5/12-7/8= | | 4x^2=4x | | -1/5-4(m+1/12)=39/10(m-11/6) | | a^2b^2-121=0 | | 9+-10x+x^4=0 | | x+6x-40=0 | | -10x+3+9x=-x-7 | | x^4-10x+9=0 |